Genesis of Legal Regulation of Domestic Violence in Ukraine - Melnykova, Dariia (Journal of Legal Studies, 2022)
The relevance of this study is due to the lack of an effective mechanism to combat domestic violence in Ukraine and an insufficiently effective system of prevention and protection against domestic violence, which creates an atmosphere of impunity and leads to the spread of this phenomenon in Ukraine. The purpose of the article is to analyze the genesis of legal regulation of domestic violence in Ukraine and determine the problems Ukraine faces during this process. The article dwells on the historical aspect of domestic violence phenomena and considers former legal regulations of it. The article also reveals some problems deriving from the historical aspect of combating domestic violence, which is still in place nowadays. Their detrimental impact on combating domestic violence is as well considered.